Strain engineering induced indirect-direct band gap transition of difluorphosphorane. (May 2020) - Liu, Yue; Lian, LiLi; Li, Da; Gao, Yan; Liu, Yan; Tian, Fubo; Duan, Defang; Li, Hongdong; Cui, Tian
Abstract: Fluorinated phosphorene exhibits very important functional properties which make it possible for the applications of phosphorene in nanoelectronic and photoelectronic fields. Here, using first-principles calculations, the mechanism of the stability of difluorphosphorane (PF2 ) is studied. It is confirmed that F-2 p electrons play the most important role in the structural stability of PF2 . The strain-stress behavior of PF2 is explored. Monolayer PF2 is a soft material with superior mechanical flexibility and can withstand a tensile strain up to 27% in the zigzag direction and 19.6% in armchair direction, which makes it have potential applications in flexible electronic devices. Remarkably, the band gap of monolayer PF2 exhibits an indirect-direct transition under tensile and compressive strains, which offers an effective method to modulate its electronic properties. The basic studies on the electronic properties of the monolayer PF2 under elastic strains are quite necessary for its future application in nanoelectronics and photoelectronics. Highlights: The stability mechanism of PF2 is studied by using first-principles calculations. Monolayer PF2 is a soft material with superior mechanical flexibility. PF2 has potential applications in flexible electronic devices. The band gap of monolayer PF2 exhibits. The strain results in an indirect-direct transition of PF2 .